Cybercrime Threats and Responsibilities: The Utilization of Artificial Intelligence in Online Crime - Muh. Fadli Faisal Rasyid; Muh. Akhdharisa SJ; Karlin Z. Mamu; Saptaning Ruju Paminto; Wahab Aznul Hidaya; Abdennour Hamadi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study examines the legal implications of artificial intelligence (AI) integration in cybercrime, focusing on the responsibilities of offenders. Through a normative analysis of relevant laws and regulations, the research reveals the challenges AI poses to law enforcement and regulatory frameworks. The findings underscore the urgent need for tailored legislation to address vulnerabilities exploited by AI-driven cybercriminals and enhance international cooperation to combat cross-border cybercrime. In conclusion, understanding and addressing the legal ramifications of AI in cybercrime are crucial. AI equips perpetrators with sophisticated tools, complicating detection and prosecution efforts. Targeted legislation is essential to close loopholes and empower law enforcement. Enhanced international collaboration is also vital to effectively address the transnational nature of cybercrime. By implementing precise legal frameworks and fostering international cooperation, policymakers and law enforcement agencies can strengthen their capacity to prevent, investigate, and prosecute AI-enabled cybercrimes, safeguarding individuals, businesses, and societies from escalating threats